Ventilatory, metabolic and kinematic responses in sprint versus distance swimmers - Hellard, P.; Lepretre, P.-M.; Avalos, M.; Seifert, L.; Hausswirth, C.; Toussaint, J. F.; Saunders, P.; Pyne, D. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The aim of this study was to compare the speed, oxygen uptake ( V02 consumption), blood lactate concentration ([La]b), and stroke rate (SR) in sprint and middle-distance swimmers. Seven male elite middle-distance swimmers (performance level=89% of the world record) and seven male sprint swimmers (performance level=88% of the world record) were recruited. Ventilatory, metabolic and kinematic parameters were obtained during a 6 x 300-m incremental swimming exercise to exhaustion. VO2 kinetics were compared between groups using a 500-m interval training set (IT-500) swum at the lactate threshold (LT). Speed at VO2max was faster for the middle-distance swimmers (1.51 ± 0.02 m/s) than the sprinters (1.34 ± 0.07 m/s). Speed at LT was also faster for the middledistance swimmers (3.1 ± 1.2 mmol/L; v LT= 1.46 ± 0.01 m/s, equivalent to 96.7 ± 0.5% of vVO2maxl than the sprinters (4.5 ± 1.5 mmol.r1; v LT= 1.22 ± 0.06 m/s, 91 ± 1.9% of vVO2max; P < 0.01). The middle-distance swimmers had a higher stroke rate at LT (36.7 ± 4.5 vs. 30.3 ± 0.7 s/min) and consumed a larger VO2max fraction (95 ± 2 vs. 84 ± 5% of VO2max; P < 0.01). A significant positive correlation was observed between dVE and dSR (r^2= 0.93, P < 0.01) in the middle-distance swimmers during the IT-500, whereas a negative relationship was observed with llstroke length (r= 0.81, P < 0.01). The middle-distance swimmers were typically 10-15% faster at the lactate threshold and at the maximal oxygen uptake. In contrast, the blood lactate concentration was 40% higher in the sprint swimmers but the stroke rate was 15% lower at the lactate threshold.